The simultaneous administration of microplastics and cadmium alters rat testicular activity and changes the expression of PTMA, DAAM1 and PREP - Venditti, Massimo; Ben Hadj Hassine, Majida; Messaoudi, Imed; Minucci, Sergio (Frontiers in Cell and Developmental Biology, 2023)
This paper confirms the damaging effects produced by MP and Cd on testicular activity in the rat. Oral treatment with both chemicals resulted in testicular damage, documented by biomolecular and histological alterations, particularly by impaired morphometric parameters, increased apoptosis, reduced testosterone synthesis, and downregulation of the steroidogenic enzyme 3β-HSD. We also demonstrated, for the first time, that both MP and Cd can affect the protein level of PTMA, a small peptide that regulates germ cell proliferation and differentiation. Interestingly, the cytoarchitecture of testicular cells was also altered by the treatments, as evidenced by the impaired expression and localization of DAAM1 and PREP, two proteins involved in actin- and microtubule-associated processes, respectively, during germ cells differentiation into spermatozoa, impairing normal spermatogenesis. Finally, we showed that the effect of simultaneous treatment with MP and Cd were more severe than those produced by MP alone and less harmful than those of Cd alone. This could be due to the different ways of exposure of the two substances to rats (in drinking water for Cd and in oral gavage for MP), since being the first contact in the animals’ gastrointestinal tract, MP can adsorb Cd, reducing its bioavailability through the Trojan-horse effect.